The Relationship Between Parenting and Peers Towards Adolescent Sexual Behavior at SMK Al-Husna, Tangerang Regency 2023 - intan, intan selfiyana; Vivi Silawati; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2023)
Background: Adolescence is a transitional period, and in any transitional period, the status of the individual is unclear and the role to be played is questioned. Today's teenage dating style tends to be risky. For example, by kissing, touching sensitive parts to having sexual intercourse before marriage. Such sexual activity violates both religious and social norms. This has to do with parenting and the role of peers. Purpose: to find out the relationship between parental parenting and the role of peers in adolescent sexual behavior at SMK AL-Husna, Tangerang regency 2023. Methods: This research is a descriptive study with a cross-sectional research design with research instruments using questionnaires. The population in this study was all class XI and XII students at SMK AL-Husna, Tangerang Regency with a total sample of 74 people. Result: Based on the results of the study, it showed that there was a significant relationship between parental parenting and adolescent sexual behavior with the results of the Spearman rho test analysis obtained a P value = 0.000 and an r value = 0.404 meaning that the correlation strength is quite strong and the direction of choleration is positive. And there is a significant relationship between the role of peers and adolescent sexual behavior as a result of the Sperman rho test analysis obtained a P value = 0.000 and an R value = 0.447, the value of r correlation strength is quite strong or the correlation direction is positive which indicates the direction. Conclusion: Students at SMK AL-Husna, Tangerang Regency, have non-risky sexual behavior that is in accordance with community norms. Parental parenting, and the role of peers have a significant relationship to the formation of sexual behavior